Impact of Fruit Smoothies on Adolescent Fruit Consumption at School. (August 2015) - Bates, Dylan; Price, Joseph
We examine the impact of serving fruit smoothies during school breakfast on fruit consumption among middle school and high school students. We draw on observational plate-waste data over a 10-week period during which fruit smoothies were introduced for breakfast at two Utah schools. Our total sample includes 2, 760 student-day observations. We find that the fraction of students eating a full serving of whole fruit increased from 4.3% to 45.1%. As such, school districts should consider offering fruit smoothies as part of a set of interventions designed to increase fruit consumption at school.